Sěrat Nitimani: Pendidikan Seks berdasarkan Etika Jawa - Insani, Nur Hanifah (Balai Bahasa Jawa Barat, 2018)
The depth study of sex education in Sĕrat Nitimani is the result of moral degradation in the society. The research describes how the ethics of sexual intercourse and Javanese wife’s dreams criteria in Sĕrat Nitimani.This descriptive qualitative research with content analysis aims to reveal the moral sex education accordance with Javanese ethics and ideal’s wife criteria in Sĕrat Nitimani.The result of the research indicates that the advice on how to choose the woman as a wife is that they should consider about ‘bobot’ (quality), ‘bibit’ (line of decent), ‘bebet’, with the same character ‘sama’, different character‘beda’, ‘dana’ (wealthy), ‘denda’; the wife’s obligations with character ‘gemi’, ‘nastiti’, ‘ngati-ati’, ‘tengen’, ‘rigen’, ‘mugen’, and ‘titi’, ‘rukti’, ‘rumanti’. The most important things of sex education is the ethics in intercourse based on moral value of Javanese society. The ethics are when doing it, it should be in a conscious, calm, earnest, patient, careful, and self-controlled. Furthermore, it is advised that it should be done in proper place, and started with clean conditions and good intentions.